« You Can Be Good Without God »: Non-Believers in 21st Century American Society - Amandine Barb (Amnis)
This article examines an often-neglected, yet increasingly visible and vocal segment of the American (ir)religious landscape: non-believers. In a general context of increasing religious disaffiliation, this historically disparate and disliked minority has managed to make its presence more assertive in the United States over the past decade. This contribution focuses on organized, militant non-believers and seeks to understand the basis, the forms, and the purposes of their surprising growing mobilization as well as its broader implications for American society at the beginning of the 21st century. Based on interviews with secular groups and relying in part on identity politics theory, the article questions, through the study of non-believers’ activism in today’s United States, the moral and social status of religion in a society apparently turning away from organized faiths, but where belief in God still remains exceptionally strong.